Basis saturation index effects on nutrition and beans yield of coffee trees - Corrêa, João Batista; Reis, Thiago Henrique Pereira; Pozza, Adélia Aziz Alexandre; Guimarães, Paulo Tácito Gontijo; Carvalho, Janice Guedes de (Coffee Science - ISSN 1984-3909, 1970)
Liming brings several benefits to coffee trees (Coffee arabica L.), especially by supplying them with calcium and magnesium and increasing the soil basis saturation index (V%). The main objective of this field experiment was to obtain the ideal basis saturation index for the coffee crop and its correlation with plant nutrition and plant production. The experiment was carried out in a clayed Red-Yellow Latossol, ";cerrado"; phase, in Lavras (Minas Gerais State), in 2000 and 2002. The Red Catuaí MG-144 cultivar was planted with 2.5 m between rows and 0.80 m between plants. The experimental design was in randomized blocks with four replications, using five treatments: 30, 40, 50, 60, and 70% of basis saturation (V%).The best basis saturation index was 55.1%. V% values above 48% increased leaf Ca, N, Fe, and B content. The increase of V% increased Ca content, the Ca:Mg relationship and soil pH, and decreased the Al3+, Al-saturation (m%), H + Al, and leaf Mn content.